Spiradenocarcinoma: SEER Study of Epidemiology, Survival, and Treatment Options - Martineau Jérôme; Walz Solange N.; Scampa Matteo; Giordano Salvatore; Kalbermatten Daniel F.; Oranges Carlo M. (MDPI, 2025)
(1) Background:
Spiradenocarcinoma is an extremely rare malignant adnexal tumor and there are only few studies on survival outcomes. Our aim was to perform an analysis of the demographic and pathological characteristics, treatment patterns, and survival outcomes of patients affected by spiradenocarcinoma.
(2) Methods:
The Surveillance, Epidemiology, and End Results program database of the National Cancer Institute was searched for all cases of spiradenocarcinoma diagnosed between 2000 and 2019. This database is considered representative of the US population. Demographic, pathological, and treatment variables were retrieved. Overall and disease-specific survival were computed according to the different variables.
(3) Results:
90 cases of spiradenocarcinoma (47 females, 43 males) were identified. Mean age at diagnosis was 62.8 years. Regional and distant disease at diagnosis were rare, occurring in 2.2% and 3.3% of cases, respectively. Surgery alone was the most frequent treatment (87.8%), followed by a combination of surgery and radiotherapy (3.3%) and radiation therapy only (1.1%). Five-year overall survival was 76.2% and five-year disease-specific survival was 95.7%.
(4) Conclusions:
Spiradenocarcinoma equally affects males and females. Regional and distant invasion rates are low. Disease-specific mortality is low and is probably overestimated in the literature. Surgical excision remains the main form of treatment.